Increasing the penetration of renewable energy sources in isolated islands through the interconnection of their power systems. The case of Pico and Faial islands, Azores. (1st September 2019) - Alves, M.; Segurado, R.; Costa, M.
Abstract: The implementation of renewable energy sources (RES) in isolated power systems, as is the case of islands, constitutes both a challenge and an opportunity. The intermittency of some RES, namely wind and solar, originates problems of grid stability and a mismatch between power demand and supply. The interconnection between isolated power systems can decrease the RES variability and, thereby, minimize the problems associated with their intermittency. In this work, the endogenous resources of the islands of Pico and Faial, in Azores, were characterized and their power systems modelled. A scenario considering the interconnection between the power systems of the two islands is proposed with the objective of increasing the share of RES power in the total power production. The scenario was modelled using EnergyPLAN and the results show that RES penetration can increase 50 percentage points by 2030 in relation to the current situation. The implementation of this scenario requires additional annual costs of about 1.29 M€. Additionally, based on the knowledge gained from this study, measures that may lead, in the long run, to the complete elimination of the overall use of fossil fuels in both islands are presented and discussed. Highlights: Interconnection between isolated power systems can decrease RES variability and intermittency. RES potential of Pico and Faial islands were characterized and their power systems modelled. Interconnection of the power systems of these islands increase RES penetration by 50 pp. This interconnection leads to additional annual costs of 1.29 M€. Measures that lead, in the long run, to complete elimination of fossil fuels in the islands are discussed.